Chilean and Transnational Performances of Disobedience: LasTesis and the Phenomenon of Un violador en tu camino. (20th January 2021) - Martin, Deborah; Shaw, Deborah
Abstract : This article analyses the performance Un violador en tu camino created by Chilean feminist theatre collective LasTesis, shared by millions and re‐staged across the globe. It explores the relationship between the original piece and theorist Rita Segato's insights on rape culture, and how it counters aspects of this culture. It examines how the transnational spread of Un violador counters tendencies of MeToo, and examines four cases of the performance's re‐staging in Latin America and beyond, showing how they make manifest the pervasiveness of rape culture as well as how groups have adapted them to speak to local issues.